2022
DOI: 10.3389/phrs.2021.1604310
|View full text |Cite
|
Sign up to set email alerts
|

Noncommunicable Diseases Prevention Policies and Their Implementation in Africa: A Systematic Review

Abstract: Objectives: To synthesize the existing evidence on NCD policy equity, policy practices, and policy implementation gaps to prevent NCDs in African countries.Methods: Following the PRISMA-Extension for equity-focused review guidelines, the authors systematically searched documentary evidence from seven databases (BMC, CINHAL Plus, Cochrane, Google Scholar, PubMed, Web of Science, and Scopus) to identify studies conducted and published on African countries between April 2013 and December 31, 2020.Results: From id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…There were a lack of key performance targets and a lack of monitoring and evaluation which resulted in poor implementation and reduced effectiveness of the guidelines. A systematic review has revealed that NCD policy development and implementation is often inadequate in Africa 38. A possible explanation is that healthcare resources are already limited and during the pandemic, these resources were diverted to address COVID-19 infections 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were a lack of key performance targets and a lack of monitoring and evaluation which resulted in poor implementation and reduced effectiveness of the guidelines. A systematic review has revealed that NCD policy development and implementation is often inadequate in Africa 38. A possible explanation is that healthcare resources are already limited and during the pandemic, these resources were diverted to address COVID-19 infections 15.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review has revealed that NCD policy development and implementation is often inadequate in Africa. 38 A possible explanation is that healthcare resources are already limited and during the pandemic, these resources were diverted to address COVID-19 infections. 15 Research conducted by the International Federation of Red Cross (IFRC) 39 during the COVID-19 pandemic looking at the role of law and policy in public health emergency preparedness and response found that the pre-existing policies and laws were inadequate to cater to the current COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, at 47% and 16% implementation rates, tobacco and physical activity policies are the highest and least implemented, respectively, in Africa. 42 Furthermore, with respect to East Africa, just 5.5% and 9.0% of dietary and physical activity policies, respectively, are implemented. 42 In view of the above, it remains a colossal challenge translating and integrating NCD policy strategies into daily operations in Africa and thus for their successful implementation; improved harmonization, sustainable funding, and robust monitoring strategies are indispensable.…”
Section: Discussionmentioning
confidence: 99%
“…[68] In the area of Non-communicable diseases policies, a systematic review of noncommunicable diseases prevention policies and their implementation in Africa revealed inadequate development of policies related to non-communicable diseases (NCDs), poor policy implementation, absence of equitable policies to address NCDs, and insufficient data collection on the prevalence, morbidity, and mortality of NCDs. [69] The continent is also off track in achieving the NCDs prevention targets by the set deadlines. [70] Nevertheless, Africa appears to be making some progress on the development NCD prevention policy, studies have reported some progress in the development of NCD prevention policies in Kenya, South Africa, Cameroon, Nigeria and Malawi, but it remains slow and uneven.…”
Section: Discussionmentioning
confidence: 99%